Role of Organizational Citizenship Behavior in Mediating The Relationship Between Job Involment and Job Performance - Purnama, Chamdan; Hakim, Lukman; Fatmah, Dinda; Rahmah, Mirhamida; Rahmah, Zakiyah Zulfa (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
Research that aims to study examined the direct and indirect effect of job involvement on job performance through organizational citizenship behavior. This study was designed as an explanator research which aims to provide an explanation of the causal relationship between variables through hypothesis testing and aims to obtain appropriate testing in drawing causal conclusions. The sample of this study was 65Â responden Fajar Printing employees using the saturated sample technique. This study uses analysis technique the PLS (Partial Least Squares regression) with the SmartPLS version 3.0 program to find that job involvement has no significant direct effect on job performance. Meanwhile, indirectly, job involvement has an effect on job performance through organizational citizenship behavior. This shows that organizational citizenship behavior is able to bridge the influence of job involvement on job performance, which can be interpreted that job involvement can have a good effect on job performance when accompanied by organizational citizenship behavior owned by company employees. The results of this study are expected to add new knowledge that will enrich the theory of human resource management, especially those related to job performance. In addition, it is hoped that these findings will help future research in paying attention to factors that can affect job performance